THE ROLE OF THE WEB AS A COMMUNICATION MEDIA IN IMPROVING PUBLIC SERVICES THE GOVERNMENT - Yuliana, Margaretha Evi; Suryani, Fajar; Ganesan, Thinesh (LPPM Universitas Duta Bangsa Surakarta, 2025)
This study aims to describe the role of the web as a communication media in improving public services provided by the Government. This research uses a descriptive method as its type and a quantitative approach. The research location is in one of subdistricts to determine the feasibility of using the web in public service. Data collection through questionnaires was an effective technique to measure and gain insight into what the respondents wanted to convey.The study titled “The Role of the Web as a Communication Media in Improving Public Services The Government,” a closed-ended questionnaire technique was chosen to make it easier and more comfortable for respondents to answer, while also simplifying data collection for the researcher. The results of the study show that the community found the web system easy to understand and use. Furthermore, there was an improvement and acceleration in the administrative services for population documentation. The existence of the population web system has enhanced public services in managing civil administration. Based on these aspects, it can be concluded that public services are very good.